The Influence of Diagnostic Evaluation Time, Specialist Consultation Duration, and Boarding Time on Ed Length of Stay Moderated by Shift Patient Volume - Jeffrey Johannes; Bernard T. Widjaja; Soegeng Wahyoedi (Syntax Corporation, 2026)
Emergency Department (ED) services face a global challenge of overcrowding, which leads to prolonged waiting times, reduced quality of care, and increased patient safety risks. One key indicator is the Emergency Department Length of Stay (ED LOS). This study aims to analyze the influence of diagnostic evaluation time, specialist consultation duration, and boarding time on ED LOS, with patient volume per shift as a moderating variable. This study employed an analytical design with a retrospective cohort approach involving 361 ED patients at Ukrida Hospital in 2024, selected using convenience sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that diagnostic evaluation time (β=0.596; p<0.001), specialist consultation duration (β=0.213; p=0.012), and boarding time (β=0.724; p<0.001) significantly affect ED LOS. Boarding time emerged as the most dominant factor with the largest contribution. In contrast, patient volume per shift showed no significant effect, either as an independent or moderating variable. These findings highlight that improving internal service efficiency, particularly patient transfer processes and diagnostic service completion, is crucial to reducing ED LOS.